SOME QUESTION ABOUT THE CUISINE OF GALICIAN ARYSTOCRATES. MENU’S OF THE LUBOMIRSKI PRINCELY FAMILY (1907–1912) (City: History, Culture, Society, 2019)
Cuisine remains one of the most critical elements of every nation’s self-identification. "We are what we eat" – the famous saying of the Greek ancient physician and doctor Hippocrates. Its sentence gives an understanding of why even gastronomic practices had a critical case on the territories of Eastern Europe occupied by Soviet Russia. Destroy national identity in all its forms. Intimidate the population and subdue their will through the famine. That was one of the aiming tasks of the totalitarian system.            Galician cuisine, which is the object of our study, has many differences in each social groups. Every of it’s had peculiarities under the influence of certain circumstances, took and gave something unique. The cuisine of the Galician aristocrats from the end of 19th and the first half of 20th centuries remains the least known for the Ukrainian’s today. We analyzed the peculiarities of their gastronomic preferences through the documents of the archive of the Polish princely family of Lubomirski.            We used anthropological, historical, and cultural methods during the study. For the first time, we introduced to scientific circulation new materials related to the lives of Andrzej and Eleonor Lubomirski in 1907–1912. Studying this issue will help to improve our knowledge of the gastronomic practices of Galician aristocrats and to learn more about their social environment, political situation. Better understand the changes that took place in Galicia before the First Great War.
Keywords: Lubomirski; aristocrats; cuisine; menu; Galicia